Menyatakan Kerajaan Allah Di Dunia Seni Budaya Pada Hari Raya Natal Di GBI ROCK Lembah Pujian Denpasar, Bali - Kobstan, Heintje Barry; Aji, Yeremia Putra (STT Kingdom, 2025)
The world that has fallen into sin makes all mankind live in the shadow of death. This has a significant impact on human life and all the activities they do. Humans and everything they do tend to gravitate towards sin and darkness. Therefore, the church is present as a representation of God who was present in the form of Jesus Christ thousands of years ago in the midst of a world that is dark, full of sin, and the shadow of death. The church exists to realize the life of God's holy kingdom for every living human being. The Church also has an important role in this regard to express God's love through the redemptive work done by Jesus Christ on the cross. On the other hand, the Church has also been chosen by God to spread the message of salvation over the power of sin and death for every human being. The Church should be able to influence all aspects of human life including the world of art and culture. This seems to be considered important because the Church and cultural arts have been side by side for a long time and are interrelated with one another. Therefore, through this research, the author invites readers to find out how the church can be a means for God to reveal his kingdom in the world of cultural arts.